Self-reported vaccination in the elderly : SABE Bogotá study, Colombia. - Gutiérrez, Carlos Cano; Reyes-Ortiz, Carlos; Borda, Miguel Germán; Arciniegas, Antonio (Colombia Medica)
Objectives: To determine the frequency of vaccination in older adults within the city of Bogotá and to estimate the association with sociodemographic and health factors. Methods: This is a secondary data analysis from the SABE-Bogotá Study, a cross-sectional population-based study that included a total of 2,000 persons aged 60 years. Weighted percentages for self-reported vaccination [influenza, pneumococcal, tetanus] were determined. The association between vaccination and covariates was evaluate by logistic regression models. Results: A total of 73.0% of respondents received influenza, 57.8% pneumococcal and 47.6% tetanus vaccine. Factors independently associated with vaccination included: 1- age (65-74 years had higher odds of receiving vaccinations, compared to 60-64 years; 2- socioeconomic status (SES) (higher SES had lower odds of having influenza and pneumococcal vaccines, compared to those with lower SES); 3- health insurance (those with contributive or subsidized health insurance had higher odds (between 3 and 5 times higher) of having vaccinations, compared to those with no insurance); 4- older adults with better functional status (greater Lawton scores) had increased odds for all vaccinations; 5- older adults with higher comorbidity had increased odds for influenza and pneumococcal vaccinations. Conclusion: Vaccination campaigns should be strengthened to increase vaccination coverage, especially in the group more reticent to vaccination or vulnerable to reach it such as the disable elder.